China's rise in the Global South the Middle East, Africa, and Beijing's alternative world order - Murphy, Dawn C. (California Stanford University Press, 2022)
As China and the U.S. increasingly compete for power in key areas of U.S. influence, great power conflict looms. Yet few studies have looked to the Middle East and Africa, regions of major political, economic, and military importance for both China and the U.S., to theorize how China competes in a changing world system. China's Rise in the Global South examines China's behavior as a rising power in two key Global South regions, the Middle East and Sub-Saharan Africa. Dawn C. Murphy, drawing on extensive fieldwork and hundreds of interviews, compares and analyzes thirty years of China's interactions with these regions across a range of functional areas: political, economic, foreign aid, and military. From the Belt and Road initiative to the founding of new cooperation forums and special envoys, China's Rise in the Global South offers an in-depth look at China's foreign policy approach to the countries it considers its partners in South-South cooperation. Intervening in the emerging debate between liberals and realists about China's future as a great power, Murphy contends that China is constructing an alternate international order to interact with these regions, and provides policymakers and scholars of international relations with the tools to analyze it
Includes bibliographical references (pages 345-379) and index.
Keywords: Middle East--Foreign relations--China.